Peran Mahasiswa Dalam Mengatasi Permasalahan Sampah Di Kota Surabaya Melalui Pendampingan Program Zero Waste - Amanda Putri Desynta; Reza Ardiansyah; Apria Yuvitar Devani Putri; Talitha Athaya Rahman; Gilang Amanda Puspanegara; Ida Syamsu Roidah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Surabaya as the second-largest city in Indonesia, faces serious challenges in waste management with daily waste generation reaching 1,800.05 tons in 2023, exceeding the capacity of Benowo landfill of 1,400 tons per day. Responding to this excess of 300 tons of daily waste, the Environmental Agency (DLH) of Surabaya City initiated the Zero Waste Village program. This program aims to increase public awareness about environmental cleanliness and waste management, implemented through collaboration between DLH and students from UPN Veteran East Java. The methods used include waste banks, composters, takakura, and processing into ecoenzymes. The program stages include sampling determination, initial waste weighing, intensive socialization, and final weighing. The results are encouraging, with a significant reduction in waste generation to an average of 0.19 kg per day per person after socialization. This success demonstrates the program's effectiveness in changing community behavior and reducing waste volume, providing hope for more sustainable waste management in Surabaya and reducing the excessive burden on the Benowo landfill.